Two-Sided Competition of Proprietary vs. Open Source Technology Platforms and the Implications for the Software Industry - Economides, Nicholas; Katsamakas, Evangelos (Management Science, 2006)
Technology platforms, such as Microsoft Windows, are the hubs of technology industries. We develop a framework to characterize the optimal two-sided pricing strategy of a platform firm; that is, the pricing strategy toward the direct users of the platform as well as toward firms offering applications that are complementary to the platform. We compare industry structures based on a proprietary platform (such as Windows) with those based on an open source platform (such as Linux), and analyze the structure of competition and industry implications in terms of pricing, sales, profitability, and social welfare. We find that, when the platform is proprietary, the equilibrium prices for the platform, the applications, and the platform access fee for applications may be below marginal cost, and we characterize demand conditions that lead to this. The proprietary applications sector of an industry based on an open source platform may be more profitable than the total profits of a proprietary platform industry. When users have a strong preference for application variety, the total profits of the proprietary industry are larger than the total profits of an industry based on an open source platform. The variety of applications is larger when the platform is open source. When a system based on an open source platform with an independent proprietary application competes with a proprietary system, the proprietary system is likely to dominate the open source platform industry both in terms of market share and profitability. This may explain the dominance of Microsoft in the market for PC operating systems.